Magnesium Lithospermate B Protects Against Cisplatin-Induced Acute Kidney Injury via Alleviating Mitochondrial Dysfunction - Shen D; Guo M; Geng X; Yu J; Zhang Z; Lin J; Lin P; Ding X; Xu X (Dove Medical Press, 2022)
Daoqi Shen,1 Man Guo,1 Xuemei Geng,1 Jinbo Yu,1- 4 Zhen Zhang,1- 4 Jing Lin,1- 4 Pan Lin,1- 4 Xiaoqiang Ding,1- 4 Xialian Xu1- 4 1Department of Nephrology, Zhongshan Hospital, Fudan University, Shanghai, People's Republic of China; 2Shanghai Institute of Kidney Disease and Dialysis (SIKD), Shanghai, People's Republic of China; 3Shanghai Key Laboratory of Kidney and Blood Purification, Shanghai, People's Republic of China; 4Shanghai Medical Center of Kidney Disease, Shanghai, People's Republic of ChinaCorrespondence: Xialian Xu; Xiaoqiang Ding, Department of Nephrology, Zhongshan Hospital, Fudan University, Shanghai Institute of Kidney Disease and Dialysis (SIKD), Shanghai Key Laboratory of Kidney and Blood Purification, Shanghai Medical Center of Kidney Disease, Shanghai, People's Republic of China, Email xu.xialian@zs-hospital.sh.cn; ding.xiaoqiang@zs-hospital.sh.cnPurpose: Apoptosis plays a critical role in cisplatin-induced acute kidney injury (AKI) and is related to mitochondrial dysfunction. Magnesium lithospermate B (Mlb), one of the most important components of Salvia miltiorrhiza Bunge, is mainly used to treat cardiovascular diseases because of its anti-apoptotic effects. The mechanism underlying the protective effect of Mlb against cisplatin-induced AKI remains unclear. In this study, we investigated the protective effect of Mlb on mitochondrial function against apoptosis caused by cisplatin-induced renal injury.Methods: Renal injury induced by cisplatin in mouse renal tubular epithelial cells (mTECs) was measured by quantifying serum creatinine levels, mitochondrial morphology, cell viability, apoptosis, Dynamin-related protein 1(Drp1) expression, etc. The cells were then administered Mlb to determine its protective effects against cisplatin-induced AKI.Results: Mlb treatment significantly reduced serum creatinine levels and pathological injury of renal, inhibited the production of malondialdehyde, and reduced the depletion of superoxide dismutase. In addition, Mlb reduced Bax/Bcl2, cleaved caspase-3/caspase-3, and maintained mitochondrial integrity after AKI. Mlb administration also improved cell viability and reduced the percentage of apoptotic cells in vitro. Furthermore, Mlb reduced mitochondrial reactive oxygen species, improved mitochondrial membrane potential, and ameliorated mitochondrial morphological abnormalities by downregulating Drp1 expression.Conclusion: These results indicated that Mlb could protect the kidneys against cisplatin-induced apoptosis by alleviating mitochondrial dysfunction.Keywords: acute renal injury, cisplatin-induced nephrotoxicity, mitochondria homeostasis, apoptosis, Salvia miltiorrhiza Bunge